Population Stereotypes for Objects and Representations: Response Tendencies for Interacting With Everyday Objects and Interfaces. (September 2019) - Vu, Kim-Phuong L.; Sun, Yuting
Objective: The objective of the study is to replicate and extend population stereotypes from a broad range of users for display-control relations of common interfaces using pictures/images of the objects. Background: Population stereotypes for display-control configurations refer to people's tendencies to associate certain control actions with display properties. An interface will benefit by being designed in a manner that is consistent with the stereotypes. The stimuli used in the present study include conceptual replications of objects that have been examined previously and new ones. Method: An online survey was designed to collect data about participants' natural response tendencies or interpretations of the meaning associated with objects, representations, and colors. Participants were obtained through MTurk from the United States, India, and UK. Results: We replicated 76% and partially replicated an additional 16% of the stereotypic responses found in prior studies. Considering the full data set, we found stereotypic responses for 62% of the stimuli that are consistent across the three countries in which the participants were located, although the strength of these stereotypes may differ by location. For the remaining 38% of the stimuli, population stereotypes still emerged for some locations. Few gender differences were found. Conclusion: Cross-cultural stereotypic responses exist for many objects, representations, and display-control configurations. However, because stereotypes can be limited to specific regions or change over time, we recommend that they be captured periodically to ensure design guidelines based on the stereotypes remain valid. Application: Designers can use the stereotypic responses to guide design decisions.